2018
DOI: 10.1002/eej.23074
|View full text |Cite
|
Sign up to set email alerts
|

Control Model for Large‐Sized Gantry Type Linear Motor Slider

Abstract: At present, many industrial carrier devices utilize linear motor sliders. However, a heavier load requires a linear motor (which is an example of a direct drive device) to get higher power, compared with a rotary motor with a ball screw slider (which is an example of an indirect drive device). In order to obtain higher power at a lower cost, a linear slider with multiple motors can be utilized, for example, a gantry type linear motor slider. Moving the gantry type slider requires two linear motors that are set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…This distortion generates a mutually repulsive force between the two axes because the reaction force on one axis is transmitted to the other axis through the top bar (joint table). A previous study derived a simulation model that reproduced this distortion and confirmed that the force between the two axes is repulsive [7]. A large repulsive force can cause the motor output forces to exceed their ratings.…”
Section: Introductionmentioning
confidence: 65%
See 4 more Smart Citations
“…This distortion generates a mutually repulsive force between the two axes because the reaction force on one axis is transmitted to the other axis through the top bar (joint table). A previous study derived a simulation model that reproduced this distortion and confirmed that the force between the two axes is repulsive [7]. A large repulsive force can cause the motor output forces to exceed their ratings.…”
Section: Introductionmentioning
confidence: 65%
“…For example, they are used for carrying thin steel plates in the steel industry [3] and, as for industrial machines, they are used in semiconductor manufacturing [2], in machining centers [4], and in devices producing large-sized liquid crystal panels [5,6]. Beneficial characteristics of linear motor sliders are quiet operation and cleanliness [7,8], which are both superior to the ball screw slider. Additionally, since the linear motor sliders are direct drive devices, they don't have couplings or elastic elements which the ball screw slider has.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations